Crystal structure of a new phen-yl(morpholino)methane-thione derivative: 4-[(morpholin-4-yl)carbothioyl]benzoic acid - GBAGUIDI, A. (My University, 2020)
4-[(Morpholin-4-yl)carbothioyl]benzoic acid, C12H13NO3S, a novel phen-yl(morpholino)methane-thione derivative, crystallizes in the monoclinic space group P21/n. The morpholine ring adopts a chair conformation and the carb-oxy-lic acid group is bent out slightly from the benzene ring mean plane. The mol-ecular geometry of the carb-oxy-lic group is characterized by similar C-O bond lengths [1.266 (2) and 1.268 (2) Å] as the carboxyl-ate H atom is disordered over two positions. This mol-ecular arrangement leads to the formation of dimers through strong and centrosymmetric low barrier O-H⋯O hydrogen bonds between the carb-oxy-lic groups. In addition to these inter-molecular inter-actions, the crystal packing consists of two different mol-ecular sheets with an angle between their mean planes of 64.4 (2)°. The cohesion between the different layers is ensured by C-H⋯S and C-H⋯O inter-actions.
Keywords: crystal structure; phenyl(morpholino)methanethione.